2021
DOI: 10.1089/ten.teb.2020.0149
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Salivary Gland Tissue Engineering: From Stem Cells to Secretome and Organoid Bioprinting

Abstract: Xerostomia or dry mouth are commonly diagnosed in head and neck cancer patients due to salivary gland (SG) epithelial injury after radiotherapy. Regenerative medicine has fetched the opportunity to replace or regenerate the SG epithelia and restore its secretory function. Early adult stem cell transplantation strategies in rodents have recently shown to improve clinical outcomes in radiotherapy-induced xerostomia in Phase 1/2 human trials. Mesenchymal stem cells from adipose tissue are the most promising, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 106 publications
0
19
0
Order By: Relevance
“…Secreted proteins or the secretome may be accessible in body fluids and are therefore considered as potential biomarkers to distinguish between healthy and diseased individuals [8]. To facilitate biomarker discovery and further assist clinicians and scientists working in these areas, we compiled and cataloged secreted proteins from the human proteome using an integrated bioinformatics approach [9,10].…”
Section: Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secreted proteins or the secretome may be accessible in body fluids and are therefore considered as potential biomarkers to distinguish between healthy and diseased individuals [8]. To facilitate biomarker discovery and further assist clinicians and scientists working in these areas, we compiled and cataloged secreted proteins from the human proteome using an integrated bioinformatics approach [9,10].…”
Section: Definitionmentioning
confidence: 99%
“…Salivary gland secretome represents a valuable new tool to measure many local soluble mediators to gain future insight into immunopathology and potentially aid in diagnosis [8]. This method could be of use to identify therapeutic targets and develop markers for stratification, prognosis and treatment response in patients [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Most complex organs, such as the lungs, kidneys, and glands, are formed by several branched, independent, organized cellular aggregates. In order to reproduce organ-specific microstructures, biomaterials should be versatile enough to allow the growth and self-organization of several cellular subtypes [46,[161][162][163]. This implies the following matrix rearrangement according to the stochastic cell growth.…”
Section: Advances In Polymer Technologymentioning
confidence: 99%
“…This issue becomes important when pluripotent cells are used in TE for differentiation and self-organization into multiple cell types in order to resemble the natural tissue. Different from biopolymers, conventional polymers fail to constantly remodel their nanostructure to be adapted to the growth and self-organizing of these cellular constructs [46,47]. Similarly, the scaffolds are expected to have a controlled degradation that slowly allows cells to exchange the matrix scaffold to their own extracellular scaffold materials [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…Murine models are currently being employed to understand mechanisms that contribute to regeneration of salivary gland tissue following damage induced by radiation, obstruction, or resection, focusing on the submandibular salivary gland [4][5][6][7][8][9] . Several therapeutic approaches are promising, including transplantation of murine salivary gland stem cells to restore function of damaged glands, as well as tissue engineering methods for the generation of functional organoids [9][10][11][12][13] . Interestingly, lineage tracing experiments in damaged glands demonstrated that cellular plasticity is an important contributor to salivary gland regeneration, and in particular to the expansion of acinar cells to replace those due to tissue damage 4,5,14,15 .…”
Section: Introductionmentioning
confidence: 99%